2021
DOI: 10.3390/plants10112444
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Strategies to Improve N Efficiency Indices in Organic Durum Wheat Grown in Mediterranean Area

Abstract: Organic farming systems are often constrained by limited soil nitrogen (N) availability. Here we evaluated the effect of foliar organic N and sulphur (S), and selenium (Se) application on durum wheat, considering N uptake, utilization efficiency (NUtE), grain yield, and protein concentration as target variables. Field trials were conducted in 2018 and 2019 on two old (Cappelli and old Saragolla) and two modern (Marco Aurelio and Nadif) Italian durum wheat varieties. Four organic fertilization strategies were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…However, similarly to Carucci et al [ 14 ], although different from Cappelli, the modern genotype Marco Aurelio showed a high protein content and adaptability to different conditions, besides high values of SDS and gluten index (see Table 2 and Table 3 ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…However, similarly to Carucci et al [ 14 ], although different from Cappelli, the modern genotype Marco Aurelio showed a high protein content and adaptability to different conditions, besides high values of SDS and gluten index (see Table 2 and Table 3 ).…”
Section: Resultssupporting
confidence: 69%
“…Concerning this, it was interesting to identify in the correlation and multivariate analysis that when some phenolic acids increase, the grain width, the grain thickness, test weight and thousand kernel weight decrease, indicating that yield-related traits are at odds with high phenolic acid concentration. This result was more evident for the modern genotypes and, among them, for Nadif and Sfinge, which resulted to be more related to morphology and yield-related components [ 14 ]. Instead, durum wheat genotypes with low yield potential as Cappelli could accumulate greater amounts of phenolic acids under the same growing conditions, as also described by Serban et al [ 33 ] for ancient wheats as more “healthy” than modern wheats in relation to their nutraceutical composition.…”
Section: Resultsmentioning
confidence: 99%
“…SPAD was consistently lower for Saragolle, which suggests a lower nitrogen use efficiency for this cultivar. Under organic farming in southern Italy, all durum wheat modern varieties outperformed old varieties Cappelli and Saragolla showing a higher nitrogen use efficiency and more responsiveness to leaf fertilization [ 42 ]. Bochicchio et al [ 43 ] reported a lower chlorophyll content index in Saragolle lucana, the same variety as in our experiment, compared to modern varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that Se uptake has cascading effects on C, N, and S uptake. In fact, several authors reported a positive effect of Se on N uptake and N utilization efficiency in wheat plants [ 60 , 61 ], probably due to the increase of the nitrate reductase activity [ 61 ]. Thereafter, increased N accumulation in wheat grains will enhance protein content [ 62 , 63 ], resulting in an increase in both gliadins and glutenins [ 64 , 65 ] that indirectly affects the rheological properties and grain quality of wheat [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water deficit significantly increases the protein content mainly due to higher rates of accumulation of grain N and lower rates of accumulation of carbohydrates; on the other hand, irrigation may decrease protein content by dilution of N with carbohydrates [ 72 ]. Later, Carucci et al [ 60 ] and Lupini et al [ 73 ] stated, however, that water stress decreased N use efficiency, N uptake efficiency, and N utilization efficiency, except for some durum wheat genotypes. Therefore, the effect of water and N assimilation interaction on protein content seems to imply a complex framework of multiple physiological processes that might be controlled by genetic factors.…”
Section: Discussionmentioning
confidence: 99%